Retensi Karyawan Generasi Milenial (Penelitian Pada Tenaga Kerja Bpjs Ketenagakerjaan Cabang Surabaya Raya) - Tri Siwi Agustina; Yudistira Adi Nugraha (Trunojoyo University of Madura, 2022)
Until mid-2020, the composition of the number of employees of the millennialgeneration, which reached 68.68% at BPJS Ketenagakerjaan Raya Surabaya Branch,had a major impact on the company's sustainability if not managed properly. Thepurpose of this study was to determine the effect of a supportive work environment on employee retention mediated by organizational engagement at BPJS Ketenagakerjaan, Surabaya Raya Branch. This research is a quantitative study using a questionnaire distributed to 86 millennial generations at BPJS Ketenagakerjaan Branch Surabaya Raya. Hypothesis testing is processed by PLS (Partial Least Square). The results showed that a supportive work environment had a positive effect on employee retention and organizational engagement could partially mediate the effect of a supportive work environment on employee retention at BPJS Ketenagakerjaan Surabaya.